Estimating the indivisible error detecting сodes based on an average probability method - Borysenko, Oleksiy; Matsenko, Svitlana; Novhorodtsev, Anatolii; Kobyakov, Oleksandr; Spolitis, Sandis; Bobrovs, Vjaceslavs (Eastern-European Journal of Enterprise Technologies, 2020)
Given the need to improve the efficiency of data transfer, there are requirements to ensure their reliability and quality under interference. One way to improve data transfer efficiency is to use noise-resistant codes, which include a closed-form expression of the Fibonacci code, a parity code, and a permanent weight code. The result of applying these types of coding produces interference-resistant end-to-end processing and transmission of information, which is a promising approach to improving the efficiency of telecommunications systems in today's environment. This paper reports the estimation of the error detecting code capability of the Fibonacci code in a closed-form expression, as well as its comparative characteristic with a parity code and a permanent weight code for a binary symmetrical channel without memory. To assess an error detecting capability of the Fibonacci code in a closed-form expression, the probability of Fibonacci code combinations moving to the proper, allowable, and prohibited classes has been determined. The comparative characteristic of the indivisible error-detecting codes is based on an average probability method, for the criterion of an undetectable error probability, employing the MATLAB and Python software. The method has demonstrated the simplicity, versatility, and reliability of estimation, which is close to reality. The probability of an undetectable error in the Fibonacci code in a closed-form expression is V=5×10-7; in a code with parity check, V=7.7×10-15; and in a permanent weight code, V=1.9×10-15, at p10=3×10- 9. The use of the average probability method makes it possible to effectively use indivisible codes for detecting errors in telecommunications systems